2022
DOI: 10.1186/s13049-021-00989-w
|View full text |Cite
|
Sign up to set email alerts
|

Do entrapment, injuries, outcomes and potential for self-extrication vary with age? A pre-specified analysis of the UK trauma registry (TARN)

Abstract: Background Motor vehicle collisions (MVCs), particularly those associated with entrapment, are a common cause of major trauma. Current extrication methods are focused on spinal movement minimisation and mitigation, but for many patients self-extrication may be an appropriate alternative. Older drivers and passengers are increasingly injured in MVCs and may be at an increased risk of entrapment and its deleterious effects. The aim of this study is to describe the injuries, trapped status, outcom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The mean age of trapped female patients was significantly higher than trapped male patients; this may influence their own ability to self-extricate due to frailty or relative immobility. 41 An additional possible explanation may include different treatment by rescuers, for example, perhaps being less likely to recommend or facilitate self-extrication for older women. Females are more likely to sit closer to the steering wheel, meaning that less movement intrusion of the dashboard and steering wheel is required to cause entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of trapped female patients was significantly higher than trapped male patients; this may influence their own ability to self-extricate due to frailty or relative immobility. 41 An additional possible explanation may include different treatment by rescuers, for example, perhaps being less likely to recommend or facilitate self-extrication for older women. Females are more likely to sit closer to the steering wheel, meaning that less movement intrusion of the dashboard and steering wheel is required to cause entrapment.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus was not achieved for some of the remaining domain areas with the most contentious being the risk stratification of patients for potential cervical spinal injury, which patients should have a collar applied, and which professional groups should be providing “in vehicle” clinical care for those that remained trapped. The subject of immobilisation, patient handling and the use of cervical collars has received much attention in the literature; with increasing acknowledgement of the incomplete evidence base for historic approaches and the support of pragmatic alternative approaches [ 9 , 17 , 28 30 , 39 , 45 51 ] . These themes are explored in more detail in the SME briefing document included in the Additional file.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns in relation to excessive patient movement have their origins in the controversial belief that such small movements may contribute to secondary spinal injury. We have previously demonstrated that unstable spinal injuries and cord injuries in isolation are very rare in injured trapped patients, whereas other time critical injuries (such as head and chest injuries) are much more common [2][3][4] . Rescue and clinical services have moved towards increased utilisation of rapid extrication methods over recent years [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Motor vehicle collisions (MVCs) are a common cause of injury and death accounting for 1.3 million deaths per year [1] . Following an MVC casualties that remain trapped in their vehicles are at risk of more severe injuries (median Injury Severity Score (ISS) not trapped 13, trapped 18) and are more likely to die (mortality non trapped 5%, trapped 8.9%) [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation